A pact with Vichy : Angelo Tasca from Italian socialism to French collaboration - Rota, Emanuel, 1970- (World War II--the global, human, and ethical dimension., 2013)
Angelo Tasca, a pivotal figure in the political history of twentieth-century Italy, and indeed the history of Europe, is frequently overshadowed by his Fascist opponent Benito Mussolini or his Socialist and Communist colleagues (Antonio Gramsci and Palmiro Togliatti). Yet, as this biography reveals, Tasca - also known as Serra, A. Rossi, André Leroux, and XX - was in fact a key political player in the first half of the twentieth century and an ill-fated representative of the age of political extremes he helped to create.